Transcendent Teacher Learner Relationships The Way of the Shamanic Teacher - O’Hara, Hunter; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2015)
"“At once humbling and empowering, this work will not fail to touch its readers and, ultimately, bring to learners authentic caring, love, hope, and a sense of being valued. The very real stories of the teachers and learners that are revealed here in their portraits leap vividly off the pages of the book. Hunter O’Hara’s bold vision of schools of transcendence is the next crucial step toward transcendent relationships and community consciousness. Readers will be inspired by this vision in Dr. O’Hara’s groundbreaking work and will be able to look within themselves for the capacity to become shamanic transcendent teachers.” Edyth James Wheeler, Ph.D. Professor Emerita, Towson University, teacher and author of Conflict Resolution in Early Childhood: Helping Children Understand and Resolve Conflicts, Merrill, 2004) “I entered into Hunter O’Hara’s work and experienced many moments that moved me deeply, at times with great joy but also with feelings of sadness in the awareness that transcendent relationships are rare and that many children and adults go through an entire lifetime without knowing one of life’s treasures- the mystery, beauty, and wonder of a loving relationship. His writing is vivid and alive and with passion and depth portrays the nature and essence of the constituents of a transcendent relationship.” Clark Moustakas, Ed.D., Ph.D., founder of the Center for Humanistic Studies (now the Michigan School of Professional Psychology) of Hunter O’Hara’s original research on transcendent teacher learner relationships)".
Keywords: Education; Education, general